Recycled Construction and Demolition Waste as Supplementary Cementing Materials in Eco-Friendly Concrete - Silvina V. Zito; Edgardo F. Irassar; Viviana F. Rahhal (Recycling, 2023)
Growing environmental awareness and scarcity of natural resources are forcing the world to migrate from linear to circular economies. The possibility of partially replacing cement with ceramic-based waste from construction and demolition waste (C&DW) is a government and industry focus. The present study analyzes the effects of including finely ground complete walls of ceramic blocks (including masonry mortars) as supplementary cementing materials (SCM) on the physical, mechanical, and transport properties (water absorption and permeability) of concrete. The replacement ratio employed was 25% by weight of cement. Studies of the hydration evolution of cement pastes support the described properties of concretes. The findings reveal that the ground ceramic-based waste from C&DW stimulates hydration at all ages. Initially, this stimulation is predominantly physical (filler effect), but in later stages, it becomes chemical (pozzolanic reaction). Based on the results obtained in this study, it is possible to produce concrete with mechanical properties comparable to those of conventional concrete at 28 days.